2020
DOI: 10.1177/1558925020969475
|View full text |Cite
|
Sign up to set email alerts
|

Resistive network model of the weft-knitted strain sensor with the plating stitch-Part 2: Resistive network model during the elongation along course direction

Abstract: Based on the static resistive network investigated in Part 1 of this series, the resistive network model of the weft-knitted strain sensor with the plating stitch is explored under the elongation along course direction, and it changes with the conductive loops’ configuration and contact situation. Since the voltage is applied at both ends of the course, under a specific stretching state, the resistive network model can be reduced to a resistance network connected in series in the course direction and parallel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…A single loop knitted structure contains three parts, termed the head, side limbs, and sinker loop, and different knitted structures have a different loop assembly and contact [ 30 , 31 , 32 ]. Hence, the length of the loop and the contact between each loop can be the main contributor affecting the resistance change and stable sensing ability of the conductive knitted fabric [ 25 , 33 ]. The change in resistance of the four different sample structures was examined to evaluate the sensitivity and stability under minimal tensile elongation.…”
Section: Resultsmentioning
confidence: 99%
“…A single loop knitted structure contains three parts, termed the head, side limbs, and sinker loop, and different knitted structures have a different loop assembly and contact [ 30 , 31 , 32 ]. Hence, the length of the loop and the contact between each loop can be the main contributor affecting the resistance change and stable sensing ability of the conductive knitted fabric [ 25 , 33 ]. The change in resistance of the four different sample structures was examined to evaluate the sensitivity and stability under minimal tensile elongation.…”
Section: Resultsmentioning
confidence: 99%
“… When the force is stretched until loops are separated from each other, the resistance is constant at the maximum value. When the fabric continues to be stressed, according to the contact resistance [ 23 , 24 ] theory as given in Equation (2), the contact pressure between the loops increases and the resistance decreases. where ( ), ( ), , and ( ) are the electrical resistivity, material hardness, number of contact points, and contact pressure between the conductive yarn, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…(2) When the force is stretched until loops are separated from each other, the resistance is constant at the maximum value. (3) When the fabric continues to be stressed, according to the contact resistance [23,24] theory as given in Equation ( 2), the contact pressure between the loops increases and the resistance decreases.…”
Section: Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Many types of research have recently reported specially treated conductive textiles as conductive elements of the flexible strain sensor. 23–26 Some attempts employed various fabrication methods, such as weaving, knitting, printing and dip-coating, by arranging the substrate and conductive materials. 27 Zhang and Long 23,28 and Wang et al.…”
mentioning
confidence: 99%